The Position of Learning and Teaching in the Al-Qur'an Perspective Thematic Tafsir Study of QS. al-'Alaq/96:1–5, QS. al-Taubah/9:122, and QS. al-Mujādilah/58:11 - Hamdi Abdillah (Journal of General Education and Humanities, 2026)
Learning and teaching are fundamental activities in Islam that possess a strong theological foundation in the Qur’an. The research problem addressed in this study is how learning and teaching are positioned in the Qur’anic perspective and what implications they have for the concept of Islamic education. This study aims to analyze the status of learning and teaching through a thematic interpretation of QS. al-‘Alaq/96:1–5, QS. al-Taubah/9:122, and QS. al-Mujādilah/58:11. The research employs a qualitative method based on library research using a thematic (maudhu‘i) tafsir approach, with descriptive-analytical analysis of Qur’anic verses as well as classical and contemporary exegetical literature. The results show that learning and teaching in the Qur’anic perspective are positioned as acts of worship, social responsibility, and means of elevating human dignity before Allah. Furthermore, educational activities in Islam are not merely oriented toward intellectual development but also integrate spiritual and social dimensions in a balanced manner. These findings affirm that ideal Islamic education should harmonize faith development, knowledge acquisition, and social responsibility.